Consumption Patterns of Enbal local food in Ohoitahit Village, North Dullah Island District, Tual City - Muh Nasrudin Lestaluhu; A.E Pattiselano; Tienni M. Simanjorang (Cita konsultindo, 2023)
This study aims to find out how the consumption pattern of local food enbal. The study was conducted in Ohoitahit Village between March and April 2023. The sample was selected as many as 60 people. Data collection was carried out by interviews and using questionnaire tools then analyzed using descriptive statistical The results showed that the people of Ohoitahit Village are no longer a staple food and are rarely consumed because they are more inclined to rice because local food is difficult to get and not available in Ohoitahit Village, North Dullah Island District, City Tual